Relationships among muscle oxygenation, blood lactate concentration, and substrate utilization during prolonged exercise below aneorobic threshold - Mimura, T.; Tanaka, S.; Ishihara, K.; Wadazumi, T.; Miyamoto, T.; Fujiwara, H.; Fujimoto, S. (Advances in Exercise and Sports Physiology, 2003)
The purpose of the study was to examine the relationships among muscle oxygenation level measured by near-infrared spectroscopy (NIRS), blood lactate concentration (LA) and substrate utilization during a prolonged 60-min steady-state exercise below the anaerobic threshold (AT). Ten healthy adult subjects (3 males and 7 females) took part in the study. The results indicated that increase in muscle oxygenation level might facilitate blood lactate disposal and fat oxidation during the prolonged exercise below AT.